Future Product Intensification Priorities For Coconut Plantation Villages' Local Conditions - Annisa Ilmi Faried; Maya Syaula; Geby Citra Ananda; Anisa Novia Rahmadani (Yayasan Multidimensi Kreatif, 2023)
Through various derivative innovations made from coconut raw materials, this service activity aims to increase public knowledge, understanding, and awareness of environmental conditions and conservation efforts in increasing the productivity of coconut products, as well as increasing the income of the people of Kebun Kelapa Village . Farmers are often held hostage by the buying and selling system set by middlemen who have little choice but to sell coconuts at perfunctory prices or debt is another forced choice. Because the dependence of farmers on the coconut industry and middlemen is getting bigger. In addition to the low price, farmers have to share the results with other coconut picking workers because they can no longer afford to pick coconuts themselves. As a result of unresolved issues in the supply chain that cause prices to drop significantly, there is a need for pricing in the market.